4, 4′, 5, 5′‐Tetrakis(guanidinyl)binaphthyl – Synthesis and Properties of Two Redox‐Active Ligands and Oxidative C–C Coupling to Perylene Derivatives. Issue 1 (30th October 2012) - Wiesner, Sven; Ziesak, Alexandra; Reinmuth, Matthias; Walter, Petra; Kaifer, Elisabeth; Wadepohl, Hubert; Himmel, Hans‐Jörg
Abstract: We report the synthesis and properties of the new redox‐active ligands 4, 4′, 5, 5′‐tetrakis(tetramethylguanidinyl)binaphthyl and 4, 4′, 5, 5′‐tetrakis( N, N′ ‐dimethylethyleneguanidinyl)binaphthyl. The first dinuclear zinc complexes were prepared. Oxidative C–C coupling of these compounds leads to perylene derivatives. Abstract : The first complexes of redox‐active tetraguanidinyl‐substituted binaphthyls were prepared. Oxidative C–C coupling leads to twofold oxidized and protonated perylene derivatives.